Controles Geológicos das Jazidas de Granitos Ornamentais da Região de Encruzilhada do Sul, RS: Origem das Variedades Comerciais do Granito Encruzilhada do Sul - PHILIPP, RUY PAULO; DE CAMPOS, ROBERTO SACKS (Pesquisas em Geociências, 2005)
<!-- .p { text-align: justify; } --> In the region of Encruzinhada do Sul, it is common the exploration of three faciological varieties of Encruzilhada do Sul Granite: porphyritic, heterogranular coarse and heterogranular very coarse. These varieties are commercially known as Rosa Encruzilhada, Bege Pérola and Coral, respectively. The petrographic analyzes and spatial disposition of the studied types indicated that the textural variations identified present a pattern of lateral zoning and are related mainly to the cooling of the granitic body and secondly to the accumulation of K-feldspar. Porphyritic sieno to monzogranite represents the cooled edges of Encruzilhada granite on embasement metamorphic rocks of Várzea do Capivarita and Arroio dos Ratos complexes. The heterogranular coarse facies represent the core portion of the body and the heterogranular very coarse facies a central and basal of the magmatic chamber, indicated by the accumulation of K-feldspar, followed by the diminishing of plagioclase, quartz and biotite teors. Beyond that, the petrographyc analysis demonstrate that the chromatic variations found in each faciology are related to the state of granite alteration, with colour variations oscilating among white and gray (sane rock), light pink to orange (signs of incipient hydrothermal and weathering alteration) and tones from light brown to very light brown (notable weathering alteration).